2013
DOI: 10.1001/jamaoto.2013.4569
|View full text |Cite
|
Sign up to set email alerts
|

Dental Caries and Head and Neck Cancers

Abstract: There is an inverse association between HNSCC and dental caries. This study provides insights for future studies to assess potential beneficial effects of lactic acid bacteria and the associated immune response on HNSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
2
17
1
1
Order By: Relevance
“…In addition, recent findings emphasize on the relationship between dental caries and some cancers e.g. head and neck and gastric cancers as well (11)(12)(13)(14). However, as recommended by American Dental Association (ADA), regular habits of tooth brushing (≥twice a day) and flossing (≥once a day) can effectively prevent these conditions (15).…”
mentioning
confidence: 99%
“…In addition, recent findings emphasize on the relationship between dental caries and some cancers e.g. head and neck and gastric cancers as well (11)(12)(13)(14). However, as recommended by American Dental Association (ADA), regular habits of tooth brushing (≥twice a day) and flossing (≥once a day) can effectively prevent these conditions (15).…”
mentioning
confidence: 99%
“…34,42,43 Our study showed that both CD8+ and FoxP3+ cell densities increase in AC as compared to NL, but a larger increase in stromal FoxP3+ cell density relative to CD8+ cells is responsible for the observed reduction in the CD8+/FoxP3+ ratio. 34,42,43 Our study showed that both CD8+ and FoxP3+ cell densities increase in AC as compared to NL, but a larger increase in stromal FoxP3+ cell density relative to CD8+ cells is responsible for the observed reduction in the CD8+/FoxP3+ ratio.…”
Section: Discussionmentioning
confidence: 55%
“…The importance of the local immune microenvironment for oral and skin carcinogenesis has been widely accepted; however, evidence for the combined roles of specific immune cell subsets is lacking at preneoplastic stages. 34,42,43 Our study showed that both CD8+ and FoxP3+ cell densities increase in AC as compared to NL, but a larger increase in stromal FoxP3+ cell density relative to CD8+ cells is responsible for the observed reduction in the CD8+/FoxP3+ ratio. Furthermore, our results suggest that FoxP3+ cell density is associated with AC independent of sun exposure, smoking status, age at diagnosis, and gender, and provides for the first time an estimate of effect size for this association.…”
Section: Discussionmentioning
confidence: 55%
“…This could be attributed to the normal commensals of the oral cavity. The mechanisms which could protect the host from the cancer include antitumorigenic or antimutagenic compounds produced by the bacteria, regulation of cytokine production, production of antimicrobial substances, clearance, inhibition of growth and downregulation of fimbrial expression of Gram-negative bacteria, production of surfactants, and stabilization of low pH [15,16].…”
Section: Discussionmentioning
confidence: 99%